Dietary introduction of gluten and casein and risk to Autism Spectrum Disorder (Research, Society and Development, 2024)
Objective: To associate the period of dietary introduction of gluten and casein with the risk of Autism Spectrum Disorder (ASD). Methodology: Retrospective cohort study that investigated children’s exposure to the consumption of foods that are sources of gluten and casein in complementary foods, and the risk of ASD between 16 and 30 months of age. The M-CHAT-R questionnaire was used to assess the risk of ASD. Association was evaluated using chi-square test. Pearson’s correlation was used to correlate the month of gluten and casein introduction with M-CHAT-R score. Result: Twenty mother-child pairs participated, with a predominance of males (80%) among the children. Two children (10%) started eating gluten or casein before six months of age. No child was at a moderate or high risk of autism according to the M-CHAT-R. There was no association between the month of introduction of gluten and casein with the risk of developing ASD. There was also no association between the month of introduction of gluten (r = -0,213, p = 0,367) or casein (r = -0,117, p = 0,625) with the total score on the M-CHAT-R, however, there seems to be a trend indicating that early introduction is correlated with a higher score on the instrument, that is, risk of ASD. Conclusion: The period of dietary introduction of gluten and casein in complementary feeding for infants is not associated with the risk of developing ASD in children aged 16 to 30 months.